On Some Issues of Analyzing Handwriting Objects Submitted for Examination in Electronic Form - V. E. Yaskina; P. I. Lakeev; L. M. Kruglov (Теория и практика судебной экспертизы)
The article discusses the issues of analyzing objects of handwriting examination provided in electronic form. The authors describe the ways of obtaining such manuscripts and their features determined by the type of the electronic documents submitted for examination. They also provide some information on the possibility of establishing if the manuscript was made using the handwriting input option, the specifics of such objects, and their differences from digitized manuscripts. The peculiarities of the stage of separate research of manuscripts presented in electronic files are outlined, as well as the problems of formulating conclusions are addressed. Finally, the authors determine the directions for further scientific research on the matters raised.